Queuing to leave: A new approach to immigration - Nayantara Sarma (IZA Journal of Development and Migration, 2021)
This paper uses queuing theory to examine the linkages between legal and illegal immigration. This approach is particularly appropriate for periods of mass migration and can be used to look at how the magnitude of people trying to migrate affects the choice between legal and illegal channels. An empirical illustration shows how origin-country conflict and past migration differently affect current legal and illegal flows. With data for Schengen countries from Eurostat for documented immigration and the European Agency for the Management of Operational Cooperation at the External Borders of the Member States of the European Union (Frontex) for illegal border crossings (IBCs), I implement a generalized method of moments (GMM) strategy using different estimates of conflict-related deaths and lagged flows of immigration as external and internal instruments, respectively. Violent conflict has a positive and significant effect on IBCs but not on documented migration flows. I find evidence of positive spillovers from the legal channel of immigration into the illegal channel but not vice versa.
Keywords: F22; F51; C6; 330; immigration; queuing theory; conflict